Managing Spiritual Growth: The Crucial Role Of Educational Management In Christian Religious Education - Rosmey Meriaty br. Sormin (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
This study explores the crucial role of educational management in Christian Religious Education (CRE) and emphasizes its significance in shaping the curriculum and objectives of CRE programs. It delves into the integral relationship between educational management and CRE, highlighting the need for systematic adherence to educational management principles within religious education. Effective educational management ensures the clear communication and achievement of goals and objectives in CRE. By organizing the curriculum, setting standards, and implementing teaching strategies, educational management fosters an environment conducive to the spiritual growth and development of students. Moreover, educational management provides guidance for educators in delivering CRE effectively. Through proper planning, coordination, and evaluation, educational management aligns the teaching-learning process with the overall objectives of education. It also facilitates resource allocation to support the implementation of CRE, ensuring that educators receive necessary training and support. The study concludes that integrating sound management principles into CRE is essential for creating meaningful learning experiences that nurture students' spiritual growth. It emphasizes the importance of recognizing the impact of educational management on the quality and effectiveness of CRE programs. Overall, the study underscores the imperative for educators and stakeholders in religious education to embrace best practices in educational management. By doing so, they can create an environment where students thrive both spiritually and academically, contributing positively to their communities and the world at large.